ADAPTATION STRATEGIES OF AR ROYYAN ISLAMIC BOARDING SCHOOL IN THE ERA OF TECHNOLOGICAL DISRUPTION - Adi Bayu Saputra, Dona; Faridi, Faridi; Tobroni, Tobroni (International Journal Multidisciplinary (IJMI), 2025)
Objective: This study aims to analyze the adaptive strategies implemented by Pondok Pesantren Ar Royyan in utilizing digital technology, particularly through optimizing social media and Artificial Intelligence (AI), to support religious outreach, educational management, and fundraising activities. Method: A qualitative descriptive method with a case study approach was employed. Data collection involved interviews, direct observations, and digital documentation analysis on the pesantren's social media platforms, including Facebook, Instagram, YouTube, and WhatsApp. Results: Findings reveal that Pondok Pesantren Ar Royyan effectively leverages social media as a means of impactful communication and outreach. Facebook emerged as the dominant platform with 4,997 followers (59%), followed by Instagram (1,665 followers, 20%), YouTube (1,440 followers, 17%), and WhatsApp (329 followers, 4%). Additionally, AI technology has been integrated to enhance creative content creation, schedule posts, analyze audience preferences, and enable automated communication. Key initiatives include establishing a Vocational Training Center for digital competence development, training media staff at BBPVP Bandung, developing a web-based application for monitoring student progress, and conducting online parenting workshops via Zoom to engage with parents. Novelty: This study demonstrates that Islamic boarding schools can effectively adapt to technological disruption by wisely adopting digital tools, strengthening religious outreach, and fostering a sustainable digital ecosystem. The research offers a reference framework for other pesantren to integrate modern technology in delivering education rooted in Islamic values.